1994
DOI: 10.1111/j.1365-2273.1994.tb01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of functional endoscopic sinus surgery

Abstract: The results of a postal questionnaire indicate an exponential rise in the practice of functional endoscopic sinus surgery (FESS) in the UK and a major complication rate of 0.23%. Cerebrospinal fluid leak was the most common serious complication accounting for 24 of the 36 reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 19 publications
2
76
0
2
Order By: Relevance
“…However, we failed to demonstrate a reduction in the postoperative complications when compared to GA alone. Although, FESS is a commonly performed procedure, close proximity of the surgical area to major blood vessels, makes good hemostasis necessary to decrease complications associated with blood loss [4]. It is usually associated with moderate pain intensity which reaches its maximum level in the first few postoperative hours [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we failed to demonstrate a reduction in the postoperative complications when compared to GA alone. Although, FESS is a commonly performed procedure, close proximity of the surgical area to major blood vessels, makes good hemostasis necessary to decrease complications associated with blood loss [4]. It is usually associated with moderate pain intensity which reaches its maximum level in the first few postoperative hours [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, side-effects related to high doses limited its usefulness. Levobupivacaine is the S(-) enantiomer of bupivacaine and clinical studies have demonstrated that both agents are equally effective [4].…”
Section: Introductionmentioning
confidence: 99%
“…In serious injuries, direct penetration trauma to the dura, serious intracranial and intracerebral complications can occur [10,18]. The commonest sites of injury in anterior cranial fossa is the cribriform plate and roof of the ethmoid sinus [19].…”
Section: Discussionmentioning
confidence: 99%
“…2 The thin lateral lamella of cribriform plate and low Ethmoid Skull Base (ESB) are potential anatomical variants that can lead to iatrogenic injuries in the form of direct penetration trauma to the Dura, serious intracranial and intra-cerebral complications during ESS. [3][4][5][6][7][8][9] ESB is defined as the orbital plate of the frontal bone, which extends from the superior attachment of Lateral Lamella of Cribriform Plate (LCP) medially to the junction of the Lamina Papyracea (LP) laterally ( Figure 1). 10 Previous studies have classified ESB as Keros I, II, III, based on the length of lateral lamella of cribriform plate or depth of olfactory fossa.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Another study quantified ESB into high (>7 mm), moderate (4 to 7 mm) and low ESB (1 to 4 mm) depending upon the height of the ESB measured from a reference plane. 13 Even though many studies reporting occurrence of low ESB causing complications during ESS exist [3][4][5][6][7][8][9] only limited studies have evaluated low ESB till date. 13,14 So the present study aims to evaluate and classify ESB preoperatively using coronal paranasal sinus CT scan images in Indian population and to deduce the relationship of ESB between side and gender.…”
Section: Introductionmentioning
confidence: 99%